Pentahelix Model in Sustainable Agrotourism Development in Rurukan, Tomohon City - Rine Kaunang; Mellisa L. G. Taroreh; Jenny Baroleh; Mukhlis Mukhlis (Postgraduate, University of Mataram, 2025)
The potential of Rurukan agro-tourism includes horticultural crops and hills with a background of mountain and lake views that have extraordinary appeal. However, the potential of agritourism has not been fully developed and optimally utilized, because it is still managed traditionally, lack of access and tourist spot infrastructure, and lack of nature conservation efforts. The purpose of this research is to formulate a pentahelix model of sustainable agro-tourism development in Rurukan, Tomohon City. This research was conducted at Rurukan Agrotourism, in East Tomohon District, Tomohon City using data analysis, namely Qualitative Descriptive Analysis. The stages in this research are; 1) Identifying the Multi Potential of Agrotourism Development in Rurukan Tomohon City, 2) Identifying the actors involved, 3) Knowing the role of actors involved in the development of sustainable agro-tourism in Rurukan Tomohon City and 4) Pentahelix Model of sustainable agro-tourism tourism development in Rurukan Tomohon City. Through this research, a Pentahelix Model of Sustainable Agritourism Development in Rurukan Tomohon City was obtained to be recommended to the Tomohon City Regional Government in sustainable tourism development policies. Pentahelix actors in the development of sustainable agritourism in Rurukan Tomohon City consist of government, academics, tourism business people, community leaders, and mass media. Four aspects that prioritize the performance of sustainable agritourism development in Rurukan are environmental, economic, cultural, and experiential aspects.